Craving and substance use among patients with alcohol, tobacco, cannabis or heroin addiction: a comparison of substance‐ and person‐specific cues. (21st April 2015) - Fatseas, Melina; Serre, Fuschia; Alexandre, Jean‐Marc; Debrabant, Romain; Auriacombe, Marc; Swendsen, Joel
Abstract Background and aims It is well established that craving increases following exposure to substance‐related 'cues', but the role of life‐styles or substance use habits that are unique to each person remains poorly understood. This study examines the association of substance‐specific and personal cues with craving and substance use in daily life. Design Ecological momentary assessment was used during a 2‐week period. Setting Data were collected in a French out‐patient addiction treatment centre. Participants A total of 132 out‐patients beginning treatment for alcohol, tobacco, cannabis or opiate addiction were included. Measurements Using mobile technologies, participants were questioned four times per day relative to craving, substance use and exposure to either substance‐specific cues (e.g. seeing a syringe) or personal cues unique to that individual (e.g. seeing the specific person with whom the substance is used). Findings Craving intensity was associated with the number of concurrently assessed substance‐specific cues (t = 4.418, P < 0.001) and person‐specific cues (t = 4.006, P < 0.001) when analysed jointly within the same model. However, only person‐specific cues were associated with increases in craving over subsequent hours of the day (t = 2.598, P < 0.05). Craving intensity, in turn, predicted increases in later substance use (t = 4.076, P < 0.001). Causal mediation analyses demonstrated that the association of cues with later substance use was mediated by craving intensity (mediated effect = 0.007, 95% confidence interval = 0.004–0.011). Conclusions Unique person‐specific cues appear to have a robust effect on craving addictive substances, and the duration of this association may persist longer than for more general substance‐specific cues. Mobile technologies provide new opportunities for understanding these person‐specific risk factors and for providing individually tailored interventions.